2011
DOI: 10.1111/j.1365-2729.2011.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Under which conditions does ICT have a positive effect on teaching and learning? A Call to Action

Abstract: Abstract'Under which conditions does ICT have a positive effect on teaching and learning?' This was the leading question of the International EDUsummIT in The Hague, the Netherlands. The bases for the discussion were the scholarly findings of the International Handbook of Information Technology in Primary and Secondary Education, a synthesis of research in the field of information and communication technology (ICT) in education. Seventy international policymakers, researchers, and practitioners developed a Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 53 publications
(74 reference statements)
4
82
0
6
Order By: Relevance
“…However, assessment persists in repeating the same mechanical models that hinder the transition from a summative to a formative type of assessment, changing only the means and tools to technological resources but the nature of learning assessment remains the same (Redecker & Johannessen, 2013;Voogt, Knezek, Cox, Knezek, & ten Brummelhuis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, assessment persists in repeating the same mechanical models that hinder the transition from a summative to a formative type of assessment, changing only the means and tools to technological resources but the nature of learning assessment remains the same (Redecker & Johannessen, 2013;Voogt, Knezek, Cox, Knezek, & ten Brummelhuis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hindering factors mentioned in our study were lack of resources, mostly in terms of time, insufficient technological knowledge, skills and competencies, infrastructure deficiencies, and issues regarding institutional policy (e.g., rewarding) -all found in several studies on ICT implementation in education (Black, Smith, & Lamshed, 2009;Govender, 2012;Surry et al, 2002;Voogt, Knezek, Cox, Knezek, & ten Brummelhuis, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Both learners and parents expect the school to stay updated and to be in line with technological developments outside the school. Voogt et al (2013b) reported that the school's policies may influence the integration of technology and it is imperative that such policies promote the positive integration of technology into lessons. There is clearly a culture of technology in the school as all the staff has introduced the use of technology.…”
Section: Integrated Discussion and Interpretationsmentioning
confidence: 99%
“…According to Tondeur et al (2012) and Nelson et al (2009), as well as (Voogt et al, 2013b), a lack of technical skills in and professional development for teachers can hinder the implementation of technology. Digital fluency is necessary to function in today's digital society and the skills learnt with technology integration in the school can be used in later in the working environment (Zhao, 2003, Polly et al, 2010.…”
Section: Favourable Conditions For Technologymentioning
confidence: 99%